A review of vlog-portfolio to develop oral fluency through peer-scaffolding - Shuib, Muhammad Asyraf; Ismail, Lilliati; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Studies in the world of English Language Teaching (ELT) that are connected to technological development are important with the diverse innovations in language teaching and learning. Thus, following a comprehensive review of literature led to the proposal of this research paper agenda. A specific focus towards learners and the learning process to achieve oral fluency as a part of communicative competence through the use of video-blogging method is employed in this paper. With frequent engagement to social media and the internet learners are actually exposed to many opportunities to exercise their language through communication. This paper will be discussing previous studies on the use of video blogging in improving speaking proficiency among ESL learners and also the province of peers to scaffold learning rendering its effectiveness. Hypothetically, some learners in an ESL environment are not well exposed to communicating using their second language which is English, L2. Therefore, this research seeks to examine the effects of using a social media platform where learners can exercise their language through video blogging with their peers. By compiling their video-blog entries in an E-portfolio, it enabled access to not only the learners, but also their peers and teacher allowing comprehensive evaluations of their performance in speaking. Furthermore, it also views underlying theories such as connectivism, scaffolding in Vygotskian Zone of Proximal Development (ZPD), which weaved together a conceptual framework for the researcher to design a module for learners to develop their full potential particularly in speaking English.